HYPERTENSION: RISK FACTORS, TREATMENT TACTICS, JNC 8 - A.E. Vasquez Abanto; S.B. Arellano Vasquez; J.E Vasquez Abanto (Bogomolets National Medical University, 2015)
Summary. At the primary level of medical care, particularly in emergency medicine, high rates of calls circulatory diseases, which are dominated by calls for hypertension. Thus, hypertension as an associated diagnosis accompanies almost every cases call for circulatory diseases. Quantitative analysis of calls serviced medical emergency brigade of disease entities leads to the conclusion that mainly serves to call the diseases of the circulatory system, hypertension with crises, diseases of the respiratory, digestive and nervous system. The percentage of circulatory diseases and hypertension with crises on all serviced calls have (for the 3 year period) such indicators: 40.84% and 25.74% respectively. In studies, published as some researchers (De la Sierra A. and Gonz6lez-Segura D.) in 2011, and other (Martell-Claros N., Galgo-Nafria A.) in 2012, were studied the risk factors for cardiovascular diseases, which emphasizes their crucial role in the occurrence of cardiovascular events. Timely diagnosis of "hypertension" is often associated with the vigilance of the doctor - after all, no clinically complaint may be. But the doctor's work is not the end. Although today the majority of patients prefer self-medication, including hypertension and relatively, work on the individual choice treatment is of utmost important part. And here the modem physician is called upon to exercise their professional medical skill as we approach this from an integrative perspective. To mainstream medical treatment of hypertension JNC 8 has developed new guidelines for the management of hypertension in adults. On the other hand, the group of medical scientists are exploring new methods, such as decreased level of the enzyme (protein) GRK2 (G-protein receptor kinase 2), suppression of the carotid body or carotid body and renal sympathetic denervation that, from the subjective point of view of the authors, deserve special attention and have a real perspective for the treatment of resistant hypertension.